2019
DOI: 10.3324/haematol.2018.209221
|View full text |Cite
|
Sign up to set email alerts
|

Co-inheritance of a-thalassemia dramatically decreases the risk of acute splenic sequestration in a large cohort of newborns with hemoglobin SC

Abstract: Co-inheritance of a-thalassemia dramatically decreases the risk of acute splenic sequestration in a large cohort of newborns with hemoglobin SC Hemoglobin SC (HbSC) is the second most common variant of sickle cell disease worldwide after Hb SS. Hb C is caused by a mutation in the seventh codon of the HBB gene [HBB:c.19G>A(p.Glu7Lys)]. The β S allele is associated with different β S haplotypes that are named according to the region in which they originated, 1 although such multicentric origin of the β S allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Some studies showed a strong modulation of α-thal in HbSβ-thal phenotype, 42 , 43 while other studies did not find significant influence. 10 , 39 , 44 We have previously observed influence of α-thal in clinical and laboratory characteristics of children with HbSS and HbSC, 8 , 9 suggesting an impact of α-thal in morbidity of SCD in our population. However, co-inheritance of α-thal had no significant influence on the laboratory and clinical parameters of children with the most frequent mutations in this study (IVS I-1 G > A and CD 39 C>T).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Some studies showed a strong modulation of α-thal in HbSβ-thal phenotype, 42 , 43 while other studies did not find significant influence. 10 , 39 , 44 We have previously observed influence of α-thal in clinical and laboratory characteristics of children with HbSS and HbSC, 8 , 9 suggesting an impact of α-thal in morbidity of SCD in our population. However, co-inheritance of α-thal had no significant influence on the laboratory and clinical parameters of children with the most frequent mutations in this study (IVS I-1 G > A and CD 39 C>T).…”
Section: Discussionmentioning
confidence: 52%
“… 7 In previous papers, we demonstrated that co-inheritance of α-thal significantly decreased the risk of cerebrovascular disease in SS children and of acute splenic sequestration in SC children. 8 , 9 However, the association of haplotypes or α-thal with the clinical course of HbSβ-thal has been only occasionaly reported. 10 …”
Section: Introductionmentioning
confidence: 99%
“…This co-transporter is markedly upregulated in sickle red cells, particularly in patients with HbSC disease 43 and is thought to be an important driver of red cell T A B L E 2 Effect of hydroxyurea therapy in patients with HbSS, and the effect co-inheritance of α-thalassemia has on the key changes seen dehydration. The mechanism by which α-thalassemia induces a milder phenotype in HbSC 39,40 has so far been poorly understood. By demonstrating a significant reduction in KCC activity in the red cells of patients with HbSC, we have identified a novel biological mechanism by which α-thalassemia may be acting in these patients to improve the cation content of the red cell and reduce the rate of hemoglobin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Co-inheritance of α-thalassemia in patients with HbSC leads to a milder phenotype, with a significantly reduced risk of acute splenic sequestration, reduced frequency of pain episodes, lower risk of osteonecrosis, and an overall improved survival rate. 39,40 Assessment of laboratory parameters has shown a reduction in mean cell volume (MCV), mean cell hemoglobin (MCH), reticulocyte percentage, white cell count (WCC), and lactate dehydrogenase (LDH), but no change in baseline hemoglobin (Hb), hematocrit, nor hemoglobin F percent (HbF %). 41,42 Hemoglobin C (HbC) is thought to contribute to intracellular HbS polymerization by encouraging red cell dehydration, in a way that hemoglobin A (HbA) does not.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that co-inheritance of α-thalassemia decreases the risk of acute splenic sequestration in HbSC disease [25]. Unlike its counterpart the homozygous SS disease, the genetic modifiers of disease severity in HbSC have not been extensively studied.…”
Section: Genetic Modifier Of Hemoglobin Sc Diseasementioning
confidence: 99%